Structured Analog CMOS Design - Stefanovic, Danica; Kayal, Maher (Analog Circuits and Signal Processing, 2008)
Structured Analog CMOS Design describes a structured analog design approach that makes it possible to simplify complex analog design problems and develop a design strategy that can be used for the design of large number of analog cells. It intentionally avoids treating the analog design as a mathematical problem, developing a design procedure based on the understanding of device physics and approximations that give insight into parameter interdependences. The proposed transistor-level design procedure is based on the EKV modeling approach and relies on the device inversion level as a fundamental design variable. Since all important design parameters can be expressed as continuous functions of the device inversion level, the design optimum as well as the technology limits can be easily found. The basic design concept consists in analog cell partitioning into the basic analog structures and sizing of these basic analog structures in a predefined procedural design sequence. The procedural design sequence ensures the correct propagation of design specifications, the verification of parameter limits and the local optimization loops. The proposed design procedure is also implemented as a CAD tool that follows this book. Finally, as a practical example, the design of analog amplifiers in a hybrid multi-bit Delta-Sigma modulator system is described in detail from system level to transistor level.